Contributions to the taxonomy and distribution of the genus Mesabolivar in southern South America (Araneae: Pholcidae) - Machado, Éwerton O.; Laborda, Álvaro; Simó, Miguel; Brescovit, Antonio D. (Zootaxa, 2013)
Two new species of Mesabolivar González-Sponga are described, M. charrua sp. nov. and M. uruguayensis sp. nov. The male of Mesabolivar tandilicus Mello-Leitão is redescribed. Notes on the natural history of the studied species are pre-sented.